1998
DOI: 10.1037/0021-9010.83.1.128
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of coaching with performance in situational employment interviews.

Abstract: Keeping you up-to-date. All APA Fellows, Members, Associates, and Student Affiliates receive-as part of their annual dues-subscriptions to the American Psychologist and APA Monitor. High School Teacher and International Affiliates receive subscriptions to the APA Monitor, and they may subscribe to the American Psychologist at a significantly reduced rate. In addition, all Members and Student Affiliates are eligible for savings of up to 60% (plus a journal credit) on all other APA journals, as well as significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 26 publications
2
49
0
Order By: Relevance
“…A search of the literature failed to identify any other studies on the effects of retesting on interview scores. In terms of coaching, two of three published studies found a positive effect on interview performance, 9 , 10 whereas the third 11 showed no effect.…”
Section: Discussionmentioning
confidence: 96%
“…A search of the literature failed to identify any other studies on the effects of retesting on interview scores. In terms of coaching, two of three published studies found a positive effect on interview performance, 9 , 10 whereas the third 11 showed no effect.…”
Section: Discussionmentioning
confidence: 96%
“…The results of one field study (Maurer, Solamon, & Troxtel, 1998) suggested that interview coaching is related to higher interview performance. More studies are needed to demonstrate effectiveness of the practice of career coaching.…”
Section: Researchmentioning
confidence: 99%
“…Insert actual ability increases might lead to practice or coaching effects (Maurer, Solamon, & Troxtel, 1998;Sackett et al, 1989). In terms of enhanced scores due to familiarity with the test, examinees may develop a better understanding of the format of the exam and the types of questions involved and may develop "tricks" to aid in responding to test questions.…”
Section: Test Repetitions and Training Performancementioning
confidence: 99%